AN ASSESSMENT OF THE ECONOMIC VIABILITY AND COMPETITIVENESS OF MODULAR REFINERY IN NIGERIA (Nigerian Journal of Technology, 2018)
Will the establishment of modular refinery in Nigeria be economically viable to withstand global economc competitiveness by 2020? What are the likely prospects regarding the revamping of the present refineries in Nigeria to produce at an established capacity of 445,000 bpsd, and the coming on stream of the Dangote 650,000 bpsd  refinery by 2020?. This paper provides analyses of the current state of the refining sector in Nigeria and the refining revolution that will take place within the next 3-5 years using data obtained from secondary sources. With a maintenance period of 31 days in a year and a PMS yield at 31.781% per barrel volume, the study revealed that with the four refineries in Nigeria working at full capacity for 334 days in a year, it can only produce 7.5 x 109 litres of PMS per annum. In the same vein the Dangote refinery, will yield about 11 x 109 litres of PMS . The import and supply analyses reveal an increase of 700,000,000 liter of PMS per year and 22.4 x 109 litres as the projected demand of PMS by 2020. The research further profiles financial analyses of a typical 10,000 bpsd modular refinery, with net income increasing from $39M in the first year to $49M in the fifth year, with dividends accumulating from $4M in the first year to $30M by the fifth year. http://dx.doi.org/10.4314/njt.v37i4.22